ANALISA PENGURANGAN TEBAL CAMRING TERHADAP DAYA DAN EFISIENSI POMPA HIDROLIK TIPE VANE PADA PUTARAN 1500 RPM - Martini, Ninik (MEKANIKA: Jurnal Teknik Mesin, 2015)
Vane type hydraulic pump is a type of Positive Displacement pumps, which pump a moving elementrotational motion. Type hydraulic vane pumps are widely used in heavy equipment units, in addition to practicalbentukya, the price is relatively cheap and very easy maintenance among their group. Vane type hydraulic pumpalso has Internal Leakage factor is small. Damage that often occurs in the field on the vane type hydraulic pump that is the wear and tear on the rotor andside plate. One way to restore the pump performance to make cuts or pemotongngan (scrap) at the surface camring,rotor and side plate wear. Cutting a maximum of 1.5 mm from the previous size. T6DC-006 pump that haskarakteristk: Volumetric displacement (V) = 21.3 cm3/rev, Max. intermittent pressure (p) = 280bar, Maxcontinuous pressure (p) = 240bar, max speed (vmax = 2500 rpm. By testing the characteristics of hydraulic pump, cutting camring of 0.5 mm, 1 mm, 1.5 mm, is able to maintain theperformance characteristics of the pump up to 80% against standartnya, at 1500 rpm rotation, output flow (Qout) at0 bar = 32 L / min, while output flow (Qout) at 140 bar = 27 liters / min. so that the pump is worn or damaged theycan be reused.Keyword :